The calcium-sensing receptor in inflammation: Recent updates - Iamartino, Luca; Brandi, Maria Luisa (Frontiers in Physiology, 2022)
The Calcium-Sensing Receptor (CaSR) is a member of the class C of G-proteins coupled receptors (GPCRs), it plays a pivotal role in calcium homeostasis by directly controlling calcium excretion in the kidneys and indirectly by regulating parathyroid hormone (PTH) release from the parathyroid glands. The CaSR is found to be ubiquitously expressed in the body, playing a plethora of additional functions spanning from fluid secretion, insulin release, neuronal development, vessel tone to cell proliferation and apoptosis, to name but a few. The present review aims to elucidate and clarify the emerging regulatory effects that the CaSR plays in inflammation in several tissues, where it mostly promotes pro-inflammatory responses, with the exception of the large intestine, where contradictory roles have been recently reported. The CaSR has been found to be expressed even in immune cells, where it stimulates immune response and chemokinesis. On the other hand, CaSR expression seems to be boosted under inflammatory stimulus, in particular, by pro-inflammatory cytokines. Because of this, the CaSR has been addressed as a key factor responsible for the hypocalcemia and low levels of 1,25-dihydroxyvitamin D (the active form of vitamin D) and PTH that are commonly found in critically ill patients under sepsis or after burn injury. Moreover, CaSR is implicated in autoimmune-hypoparathyroidism, more recently also in patients treated with immune-checkpoint inhibitors. Given the tight bound between the CaSR, calcium and vitamin D metabolism, we also speculate about their roles in the pathogenesis of SARS-COVID-19 infection and their impact on patients' prognosis. Finally, we will explore the therapeutic potential of pharmacological targeting of the CaSR for the treatment and management of aberrant inflammatory responses.